The Development of a Two-Tier Diagnostic Test to Detect Student’s Misconceptions In Learning Process - Tukiyo Tukiyo; Mukhtar Efendi; Everhard Markiano Solissa; Ika Yuniwati; Syatria Adymas Pranajaya (Mudir : Jurnal Manajemen Pendidikan, 2023)
The goal of this study was to create a two-tier multiple-choice diagnostic instrument to identify students' misconceptions. In developing this instrument, 207 students were involved in interviews, essay tests, multiple-choice tests with open reasons, and two-tier diagnostic tests. The Cronbach's alpha equation yields a dependability value of 0.764 for the 16 valid questions. Based on the misconception analysis of the six main concepts, the majority of students had misconceptions. Overall, the instrument is quite effective for determining student misconceptions. In order to assess students' misconceptions about acids and bases, this instrument might be used as a substitute test.